Enamel-renal-gingival syndrome and FAM20A mutations - Piranit Nik Kantaputra (2018)
The enamel-renal syndrome of amelogenesis imperfecta (AI) and nephrocalcinosis, and the amelogenesis imperfecta-gingival fibromatosis syndrome have both been associated with mutations in FAM20A. We report on two unrelated Thai patients with three novel and one previously reported mutations in FAM20A with findings suggesting both disorders, including hypoplastic AI, gingival fibromatosis, unerupted teeth, aggressive periodontitis, and nephrocalcinosis/nephrolithiasis. Additional findings consisted of a supernumerary premolar, localized aggressive periodontitis, thin alveolar bone, vitamin D deficiency-associated hyperparathyroidism, and heterotopic calcification in other tissues, including lungs, dental pulp, gingiva, dental follicles, and periodontal tissues, and early cessation of limited menstruation. Greater promotory activity of urine on calcium oxalate crystal growth compared to controls may help to explain the pathogenesis, and suggest that FAM20A mutations can contribute to nephrocalcinosis/nephrolithiasis. Our findings expand the phenotypic spectrum of FAM20A mutations. Since both of our patients and a large number of previously reported cases had all the important features of both syndromes, including AI, renal anomalies, and gingival fibromatosis, we are convinced that these two disorders actually are the same entity. The name of enamel-renal-gingival syndrome is suggested. © 2013 Wiley Periodicals, Inc.